Membrane fouling by organic macromolecules - Tan, Jong Sheng. (2009)
Organic macromolecules, which exist abundantly in raw water, have been identified as one of the major foulants that leads to formation of cake layers on nanofiltration membrane. In this study, experiments were carried out to investigate the effect of feed solution composition, defined here as solution pH, ionic strength and divalent cation concentration on the permeability of negatively charged membrane surface. Bovine serum albumin (BSA) was chosen as model foulant to represent proteins in organic macromolecules. The degree of membrane fouling was quantified by comparing the flux decline rate at certain period of time under varying experimental conditions (pH, divalent cation concentration and ionic strength). Permeate conductivity have also been measured to examine the rejection tendency of nanofiltration membrane at specific solution chemistry. Experimental results suggest that (i) Membrane fouling was found to reach the peak at solution pH that close to isoelectric point (pH 4.7 – 5.1) of BSA. (ii) BSA fouling of nanofiltration membrane intensified at higher ionic strength and divalent cation concentration. (iii) Intermolecular electrostatic repulsive force decreased as the solution pH approaching isoelectric point of BSA. (iv) The effect of solution chemistry on membrane fouling was more significant at higher flux. It has been further demonstrated that the tendency of membrane fouling was associated with electric double layer compression as well as the convective flow towards the membrane.